Extractable organic matter of Standard Reference Material 1649a influences immunological response induced by pathogen-associated molecular patterns - Ulrich, Kerstin; Wölfle, Sabine J.; Mayer, Anja; Heeg, Klaus; Braunbeck, Thomas; Erdinger, Lothar (Environmental science and pollution research, 2010)
Background, aim, and scopeLungs are permanently and simultaneously challenged by airborne microorganisms and airborne pollutants. Temporal increase of airborne particulate matter (APM), a potential carrier for extractable organic matter (EOM), degrades the situation of pulmonary patients. The Ah receptor (AhR) has been described as an important factor influencing the immunological challenge by viral infections. Molecular mechanisms underlying epidemiological observations are not well understood. Cytokine secretion (IL-6, IL-8, and TGF-β) from human bronchial epithelial cells (Beas2B) was determined as an indicator for immune responses upon co-stimulation with an artificial analog of viral dsRNA [polyinosinic/polycytidylic acid, (PIC)] and EOM of Standard Reference Material 1649a (SRM). Since polycyclic aromatic hydrocarbons are major components of APM usually acting via the AhR, particular focus was on AhR involvement.Materials and methodsCytokine secretion was demonstrated by enzyme-linked immunosorbent assay. To mimic the activation of organic matter during contact of particles with the human lung, Soxhlet extraction of SRM was performed. In some experiments, the AhR was blocked by α-naphthoflavone.ResultsMicrobial stimulation (PIC) induced Beas2B cytokine release, whereas isolated exposure to EOM of APM did not. Co-stimulation with EOM and PIC increased IL-8 secretion, whereas neither IL-6 nor TGF-β was affected. Blocking of the AhR suppressed the release of IL-8.DiscussionOrganic compounds adsorbed on airborne particulate matter influence the cytokine secretion of lung epithelial cells induced by pathogen-associated molecular patterns.Recommendations and perspectivesFurther investigation of these observations is required to understand the molecular mechanisms underlying adverse health effects of APM reported in epidemiological studies.